VARIASI KETEBALAN KARBON AKTIF AMPAS TEBU UNTUK MENINGKATKAN KUALITAS AIR SUMUR (Uji Coba Pengolahan Air Sumur Di Kecamatan Semampir Kota Surabaya) - Reksa Nirmala Sandy; Darjati .; Ernita Sari (Poltekkes Kemenkes Surabaya, 2017)
ABSTRACTOne way to process water is employing adsorption techniques by using activated carbon to removeorganic pollutants. Cellulose and lignin content in the sugarbcane waste can be converted into activated carbonadsorption that plays important role during the process. This study aims at analyzing the thickness effectivenessof sugarcane waste activated carbon as adsorbent in improving the quality of ground water.This research is a pre-experimental research which employs one group pretest -posttest design. Datacollection is done by laboratory tests that followed by statistical analysis using ANOVA test.The parameters being analyzed include color, odor, taste, TDS, turbidity, pH, Fe, Mn and OrganicSubstance. Those Parameters were analyzed, compared to Permenkes No. 416 / Menkes / Per / IX / 1990 aboutTerms and Water Quality Monitoring. Comparative analysis indicates that the color, smell, taste, TDS, turbidity,pH, Fe, Mn and organic substance meets the standards chronologically TCU 11.58, 389.25 mg / L, 1.15 NTU , 7,0.131 mg / L, 0.013 mg / L, 0,729 mg / L. Statistical test analysis result shows that variations in the thickness ofsugarcanewaste activated carbon affect the analyzed parameters.It can be concluded that the quality of ground water after processing increase to meet the standards ofPermenkes No. 416 / Menkes / Per / IX / 1990 about Terms and Water Quality Monitoring, with 70 cm thickeffectiveness. It is suggested to the society to be able to perform simple water processing to get clean water thatmeets the standards.Keywords : Ground Water, Sugarcane Waste, Activated Carbon, Adsorbsi